2014
DOI: 10.1002/jcla.21823
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Mass Index on the Activated Clotting Time Under Weight‐Based Heparin Dose

Abstract: The results of our study have shown that a standardized dosing nomogram that uses the actual body weight to calculate the heparin doses may result in UFH overdose for patients with higher BMI compared to patients with lower BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…12 Similarly, Hong et al reported that actual body weight-based heparin dosing resulted in overdoses in the higher BMI group compared with the lower BMI group. 25 Consistently, we observed that on ROC curve analysis, BMI over 29.4 kg/m 2 predicted the presence of hematoma with a slightly lower sensitivity and specificity. In the obese population, guiding the heparin doses according to ideal body weight, amended weight, or blood volume may be considered to prevent hemorrhagic complications but still, it was not applied in practical use and trials.…”
Section: Discussionsupporting
confidence: 77%
“…12 Similarly, Hong et al reported that actual body weight-based heparin dosing resulted in overdoses in the higher BMI group compared with the lower BMI group. 25 Consistently, we observed that on ROC curve analysis, BMI over 29.4 kg/m 2 predicted the presence of hematoma with a slightly lower sensitivity and specificity. In the obese population, guiding the heparin doses according to ideal body weight, amended weight, or blood volume may be considered to prevent hemorrhagic complications but still, it was not applied in practical use and trials.…”
Section: Discussionsupporting
confidence: 77%
“…Indeed, ACT is accurate for monitoring UFH effects, as a strong and reproducible correlation between ACT and UFH anti‐Xa activity was repeatedly reported . However, several factors affect the anticoagulant response to fixed or weight‐adjusted UFH dose . Bloemen et al described a large interindividual disparity of UFH pharmacodynamic effect with coefficients of variation of 24% to 43% .…”
Section: Discussionmentioning
confidence: 99%
“…15,16 However, several factors affect the anticoagulant response to fixed or weightadjusted UFH dose. 17,18 Bloemen et al described a large interindividual disparity of UFH pharmacodynamic effect with coefficients of variation of 24% to 43%. 19 Moreover, like us, Gabus et al showed that more than half of the patients with interrupted VKA and LMWH bridging undergoing AF catheter ablation remained with ACT <300 seconds at 20 minutes after the initial UFH bolus.…”
Section: Flutter Catheter Ablationmentioning
confidence: 99%